Why all integration problems have integrand?

Calculus Level 5

π / 3 π / 3 π + 4 x 3 2 cos ( x + π 3 ) d x \displaystyle\int_{-\pi/3}^{\pi/3} \dfrac{\pi+4x^3}{2-\cos\left(|x|+\frac{\pi}{3}\right)}\ dx

If the above integral can be expressed as a π b tan 1 ( 1 c ) \dfrac{a\pi}{\sqrt{b}} \tan^{-1} \left(\frac{1}{c}\right) for positive integers a , b , c a,b,c with a , b a,b coprime and prime c c . Find a + b + c a+b+c .


The answer is 9.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Aman Rajput
Jun 7, 2015

π / 3 π / 3 π + 4 x 3 2 cos 2 ( x + π 3 ) d x \displaystyle\int\limits_{-\pi/3}^{\pi/3} \frac{\pi + 4x^3}{2 - \cos^2(|x| + \frac{\pi}{3})} dx = π π / 3 π / 3 1 1 + 2 s i n 2 ( x 2 + π 6 ) d x + π / 3 π / 3 4 x 3 1 + 2 s i n 2 ( x 2 + π 6 ) d x =\pi\int\limits_{-\pi/3}^{\pi/3} \frac{1}{1 + 2sin^2(\frac{|x|}{2} + \frac{\pi}{6})} dx + \int\limits_{-\pi/3}^{\pi/3} \frac{4x^3}{1 + 2sin^2(\frac{|x|}{2} + \frac{\pi}{6})} dx The second integral is 0 0 (zero), since it is an odd function.

We are left with first integral which is splitted into two parts....

= π [ π / 3 0 1 1 + 2 s i n 2 ( x 2 + π 6 ) d x + 0 π / 3 1 1 + 2 s i n 2 ( x 2 + π 6 ) d x ] \displaystyle = \pi[\int\limits_{-\pi/3}^0 \frac{1}{1 + 2sin^2(\frac{-x}{2} + \frac{\pi}{6})} dx + \int\limits_0^{\pi/3} \frac{1}{1 + 2sin^2(\frac{x}{2} + \frac{\pi}{6})} dx]

Substituting x 2 + π 6 = u \frac{-x}{2} + \frac{\pi}{6} = u and x 2 + π 6 = v \frac{x}{2} + \frac{\pi}{6} = v , we get

= 2 π π / 6 π / 3 2 1 + sin 2 u d u =2\pi {\int\limits_{\pi/6}^{\pi/3} \frac{2}{1 + \sin^2u} du}

because a b f ( u ) d u = a b f ( v ) d v \int_a^b f(u)du = \int_a^b f(v)dv

Solving the integral , we easily get the result = 4 π ( 4 tan 1 3 π 4 3 ) =4\pi(\frac{4\tan^{-1}{3} - \pi}{4\sqrt{3}})

which can be written in the form of = 4 π 3 ( tan 1 3 π 4 ) =\frac{4\pi}{\sqrt{3}} (\tan^{-1}{3} - \frac{\pi}{4})

which on further simplification yeilds,

= 4 π 3 tan 1 1 2 =\frac{4\pi}{\sqrt{3}} \tan^{-1}{\frac{1}{2}}

Therefore, a + b + c = 4 + 3 + 2 = 9 a+b+c = 4+3+2 = 9

same ques.... this one diff formats!!

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...